Effect of the combination of several irrigants on dentine surface properties, adsorption of chlorhexidine and adhesion of microorganisms to dentine - Tartari, T.; Wichnieski, C.; Bachmann, L.; Jafelicci, M. [UNESP]; Silva, R. M.; Letra, A.; van der Hoeven, R.; Duarte, M. A. H.; Bramante, C. M. (Wiley-Blackwell, 2018)
Aim To investigate the effects of combinations of several irrigants on the roughness and wettability of dentine, adhesion of Enterococcus faecalis and Candida albicans and adsorption of chlorhexidine (CHX) to the dentine. Methodology Results Bovine dentine samples were prepared and their surface roughness standardized. The samples were distributed in groups (n = 10) and subjected to one of the following irrigation protocols: G1 - saline solution; G2 - sodium hypochlorite (NaOCl); G3 - NaOCl + ethylenediaminetetraacetic acid (EDTA); G4 - NaOCl + peracetic acid (PAA); G5 - NaOCl + 1-hydroxyethylidene-1,1-diphosphonic acid (HEDP); G6 - NaOCl + EDTA + CHX; G7 - NaOCl + PAA + CHX; G8 - NaOCl + HEDP + CHX; and G9 - mixture of NaOCl + HEDP. After treatments, roughness and wettability were measured. In order to evaluate the adhesion of microorganisms to dentine, new dentine samples were prepared and after 2 h of contact with the microorganisms, were analysed using a confocal laser scanning microscope and the number of microorganisms adhering to the surfaces were determined. Absorption spectra were collected by attenuated total reflectance of Fourier-transform infrared spectroscopy before and after immersion of other dentine samples in each solution of G6, G7 and G8 and in a solution of 2% CHX at various time intervals. The areas of the band associated with CHX with the peak at 1492 cm(-1) were calculated between 1479 and 1500 cm(-1) of the spectral range. The data obtained in all experiments were subjected to one-way ANOVA (alpha < 0.05). The values of the CHX band were also subjected to one-way repeated measures ANOVA (alpha < 0.05). Saline solution, NaOCl, HEDP and CHX did not alter the roughness of the dentine (P > 0.05), whilst EDTA and PAA did (P < 0.05). Dentine surface wettability increased after the use of all irrigants compared to saline solution (P < 0.05), with HEDP causing the greatest increases (P < 0.05). The adhesion of E. faecalis was favoured on surfaces treated with only saline solution and NaOCl, and on samples that had decalcifying agents as the final irrigant (P < 0.05). The adhesion of C. albicans was highest on surfaces treated with only saline solution and on surfaces that had NaOCl used as the last irrigant (P < 0.05). The use of CHX as a final irrigant reduced the adhesion of both microorganisms. The roughness and wettability did not influence the adhesion of the microorganisms tested. The adsorption of CHX to the dentine was significant after 1 min of immersion of the mineralized samples in the irrigant (P < 0.05), and the use of chelating agents prior to CHX potentiated this adsorption. Conclusions The irrigation solutions had a variable effect on the properties of dentine, on the adhesion of E. faecalis and C. albicans and the adsorption of CHX to the dentine surface.
Keywords: bacterial adhesion; Candida albicans; chlorhexidine; Enterococcus faecalis; irrigation solutions; surface properties